2021
DOI: 10.1038/s41698-021-00157-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic transcriptomic biomarkers in soft tissue sarcomas

Abstract: Soft tissue sarcomas (STS) are rare and heterogeneous tumours comprising over 80 different histological subtypes. Treatment options remain limited in advanced STS with high rates of recurrence following resection of localised disease. Prognostication in clinical practice relies predominantly on histological grading systems as well as sarcoma nomograms. Rapid developments in gene expression profiling technologies presented opportunities for applications in sarcoma. Molecular profiling of sarcomas has improved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 86 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…Novel circulating biomarker candidates such as tumor-derived extracellular vescicles (EVs) and circulating tumor cells (CTCs) have been studied in STS [ 173 , 174 , 175 ]. Even though data regarding the prognostic significance of CTC isolation in STS are limited, a correlation between CTC presence and disease progression has been observed [ 176 , 177 ].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel circulating biomarker candidates such as tumor-derived extracellular vescicles (EVs) and circulating tumor cells (CTCs) have been studied in STS [ 173 , 174 , 175 ]. Even though data regarding the prognostic significance of CTC isolation in STS are limited, a correlation between CTC presence and disease progression has been observed [ 176 , 177 ].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Bertucci et al 2017 [ 183 ] showed that PDL1 mRNA expression is heterogenous in STS, and is an independent prognostic factor of metastatic relapse. Recently clinically evaluated transcriptomic biomarker signatures such as Complexity INdex in SARComas (CINSARC), genomic grade index and hypoxia-associated signature can be integrated with biomarkers of targeted therapy enhancing prognostication [ 173 ].…”
Section: Biomarkers In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed upregulation of the COL1A1 mRNA level in lung cancer tissues compared with normal lung tissues in the Rohrbeck Lung dataset ( Figure 2 B ). Additionally, Merry et al identified that a characteristic amplification of sequences from chromosome 17q, demarcated by the COL1A1 gene, was associated with elevated expression of the COL1A1 in dermatofibrosarcoma protuberans (DFSP) 20 . These observations suggested that the COL1A1 protein may be highly expressed in lung cancer tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Soft tissue sarcomas (STSs) are a heterogeneous group of rare tumors arising from mesenchymal tissues [1]. STSs can originate from any human body location and, with more than 80 histological subtypes of STSs, data regarding novel biomarkers of strong prognostic and therapeutic value are very limited [2,3]. The most prevalent histological subtypes of STSs include liposarcoma, undifferentiated pleomorphic sarcoma, and leiomyosarcoma [4].…”
Section: Introductionmentioning
confidence: 99%